Stress tolerant virulent strains of Cronobacter sakazakii from food - Fakruddin, Md (Biol Res, 2014)
BACKGROUND: Cronobacter sakazakii is considered as an emerging foodborne pathogen. The aim of this study was to isolate and characterize virulent strains of Cronobacter sakazakii from food samples of Bangladesh. RESULT: Six (6) Cronobacter sakazakii was isolated and identified from 54 food samples on the basis of biochemical characteristics, sugar fermentation, SDS-PAGE of whole cell protein, plasmid profile and PCR of Cronobacter spp. specific genes (esak, gluA, zpx, ompA, ERIC, BOX-AIR) and sequencing. These strains were found to have moderately high antibiotic resistance against common antibiotics and some are ESBL producer. Most of the C. sakazakii isolates were capable of producing biofilm (strong biofilm producer), extracellular protease and siderophores, curli expression, haemolysin, haemagglutinin, mannose resistant haemagglutinin, had high cell surface hydrophobicity, significant resistance to human serum, can tolerate high concentration of salt, bile and DNase production. Most of them produced enterotoxins of different molecular weight. The isolates pose significant serological cross-reactivity with other gram negative pathogens such as serotypes of Salmonella spp., Shigella boydii, Shigella sonnei, Shigella flexneri and Vibrio cholerae. They had significant tolerance to high temperature, low pH, dryness and osmotic stress. CONCLUSION: Special attention should be given in ensuring hygiene in production and post-processing to prevent contamination of food with such stress-tolerant virulent Cronobacter sakazakii. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/0717-6287-47-63) contains supplementary material, which is available to authorized users.